Associations between body mass index, weight loss and overall survival in patients with advanced lung cancer. Issue 6 (20th October 2022) - Oswalt, Cameron; Liu, Yingzhou; Pang, Herbert; Le‐Rademacher, Jennifer; Wang, Xiaofei; Crawford, Jeffrey
Abstract: Background: Weight loss (WL) has been associated with shorter survival in patients with advanced cancer, while obesity has been associated with longer survival. Integrating body mass index (BMI) and WL provides a powerful prognostic tool but has not been well‐studied in lung cancer patients, particularly in the setting of clinical trials. Methods: We analysed patient data ( n  = 10 128) from 63 National Cancer Institute sponsored advanced non‐small cell lung cancer (NSCLC) and small cell lung cancer (SCLC) trials. Risk matrices were created using BMI and WL percentage, which were divided into 'grades' based on median survival. Relationships between survival, BMI and WL percentage were examined using Kaplan–Meier estimators and Cox proportional hazards (PH) models with restricted cubic splines. Results: For NSCLC, a twofold difference was noted in median survival between the BMI > 28 and WL ≤ 5% group (13.5 months) compared with the BMI < 20 and WL > 5% group (6.6 months). These associations were less pronounced in SCLC. Kaplan–Meier curves showed significant survival differences between grades for both NSCLC and SCLC (log‐rank, P  < 0.0001). In Stage IV NSCLC, Cox PH analyses with restricted cubic splines demonstrated significant associations between BMI and survival in both WL ≤ 5% ( P  = 0.0004) and >5% ( P  = 0.0129) groups, as well as in WL > 5% in Stage III ( P  = 0.0306). In SCLC, these relationships were more complex. Conclusions: BMI and WL have strong associations with overall survival in patients with advanced lung cancer, with a greater impact seen in NSCLC compared with SCLC. The integration of a BMI/WL grading scale may provide additional prognostic information and should be included in the evaluation of therapeutic interventions in future clinical trials in advanced lung cancer.